ACCOUNTING FOR DECISIONS. - Raun, Donald L. (The Accounting Review, 1961)
Abstract Successful decisions are the hope of every manager. Snap decisions indicate a disregard for scientific thinking and reliance upon intuition and chance, or an unusual mental ability to simulate the problem, determine the strategic factors, and evaluate the alternatives. Historically, accounting has developed as the result of a specific need. The balance sheet model was presented to satisfy a need for financial information. Each ledger account is a model, or method, of measuring all transactions (the relevant factors) of a business which are relevant to the respective ledger account as it is specifically defined and by a method recognized as generally accepted by the accounting profession. To identify a specific ledger account as meaningful, the account must be defined in terms of the relevant business transactions which the model (ledger) will summarize, as well as the specific method or methods by which these relevant transactions will be measured. Finally, the specific ledger account must be defined as a relevant factor in the total accounting system, including its relationship to all other relevant factors of the system. Thus the accounting system itself, as we identify it, consists of a model summarizing the relationships of a large number of smaller models presumably for some specific purpose.